From German to Turkish loan words in Turkish dictionaries - An evaluation [Aus dem Deutschen ins Türkische übernommene wörter in türkischen wörterbüchern - Eine bestandsaufnahme] - (:unkn) unknown (My University, 2008)
This article deals with the current inventory of German loan words in Turkish. Since three new Turkish dictionaries were published simultaneously by three different institutions at the end of 2005, it is now interesting to see how these dictionaries differ with respect to how they treat German loan words. .